Energy-Optimal 3D Path Planning for MAV with Motion Uncertainty - Yamin Li; Bowen Sun; Ping Xia; Yang Yang (Complexity)
Practical applications of microaerial vehicle face significant challenges including imprecise localization, limited on-board energy, and motion uncertainty. This paper focuses on the latter two issues. The core of proposed energy-optimal path planning algorithm is an energy consumption model deriving from real measurements of a specific quadrotor and utilizing a 2D Gaussian distribution function to simulate the uncertainty of random drift. Based on these two models, we formulate the optimal path traversing the 3D map with minimum energy consumption using a heuristic ant colony optimization. Multiple sets of contrast experiments demonstrate the effectiveness and efficiency of the proposed algorithm.